2017
DOI: 10.3126/jcmsn.v13i4.18122
|View full text |Cite
|
Sign up to set email alerts
|

Flexible intramedullary nailing for femoral diaphyseal fractures in children

Abstract: Background & Objectives: Although various treatment options are available for the treatment of femoral diaphyesal fractures in children, the titanium flexible nailing has gained popularity because it is safe, easy procedure with rapid recovery and high success rate. The aim of this study was to evaluate the outcome of titanium elastic nails in treating paediatric femoral diaphyesal fractures at Patan Hospital.Materials & Methods: There were 35 cases which were all fixed with titanium flexible intramedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Radiological evaluation showed that most cases (80.0%) achieved union within 7-10 weeks, consistent with findings by [13]. Partial weight-bearing was advised at 4 weeks for most patients (63.3%), with the rest advised at 8 weeks.…”
Section: Discussionsupporting
confidence: 83%
“…Radiological evaluation showed that most cases (80.0%) achieved union within 7-10 weeks, consistent with findings by [13]. Partial weight-bearing was advised at 4 weeks for most patients (63.3%), with the rest advised at 8 weeks.…”
Section: Discussionsupporting
confidence: 83%